2020
DOI: 10.1002/ncp.10590
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Support Therapies on the Medication Administration Record: Impacts on Staff Perception of Nutrition Care

Abstract: Background It has been reported that many hospitals in the United States have fragmented and ineffective ordering, administration, documentation, and evaluation/monitoring of nutrition therapies. This paper reports on a project to investigate if perceived hospital staff awareness and documentation of nutrition support therapies (NSTs) improves by including them as part of the medication administration record (MAR). Methods Surveys were conducted with nursing staff, physicians, and dietitians before and after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Information about missing products can be relayed to food service staff for service correction. As providers become more aware of the status of administration (or nonadministration) of therapies, they can make decisions and provide timely adjustments in care plans 28,29,32 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Information about missing products can be relayed to food service staff for service correction. As providers become more aware of the status of administration (or nonadministration) of therapies, they can make decisions and provide timely adjustments in care plans 28,29,32 …”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, EN delivery is notoriously underdelivered, underdocumented, and underconsumed. 13,19,26,[28][29][30] In fact, Costello et al 31 (2018) conducted a recent survey across federal agencies and found nutrition supplements are inconsistently reconciled, documented, and tracked within the federal facility's EHR systems. In our process improvement project, the addition of nutrition therapies on the MAR/BCMA seeks to meet this unmet need by capturing these products within the MAR and requiring safer nursing administration and documentation practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors are known to affect patient comfort (especially nausea), insulin resistance, and LOS, since a “diet as tolerated” (DAT) assessment is needed for discharge. Recording ONS on the Medication Administration Record or a separate Nutrition Administration Record may facilitate POI reduction, early post-operative enteral feeding, and DAT evaluation [ 41 ]. Finally, a recent report provides a useful conceptual framework for studying the relationships of core elements bundled in ERAS colorectal programs based on variations in the primary outcomes of three sub-populations [ 42 ].…”
Section: Discussionmentioning
confidence: 99%